PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN STUDI PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MALANG - Erik Ibrahim; abd kodir djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
This study aims to determine the effect of compensation, motivation, effect of compensation on employee performance, and motivation on employee performance at the Office of Population and Civil Registration in Malang. Based on the results of the analysis found that compensation has a positive effect on employee performance, motivation has a positive and significant effect on job satisfaction, compensation has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, Based on the results of the study, the company Office of Population and Civil Registration (DISPENDUK CAPIL) Malang City should provide fair compensation, motivate employees with promotion of position, to improve maximum work quality.